Automatización del revestimiento de ejes metálicos con polímeros, para la elaboración de rodillos en la planta industrial "Alfiza Revestimientos Industriales" - Chimbo Romero, Gonzalo Gabriel (2016)
Industrial Coatings is a company dedicated to the coating of metal shafts with polymers, ALFIZA their production lines are fully empirical so it has decided to renew the traditional process by one machine. The renovation project aims to increase production, optimize raw materials and improve the working conditions of the operator using their full physical and intellectual capacity. For this purpose, system automation coated metal shafts automatically, to control and synchronize the rotational speed of the jaw chuck and the forward speed of a saddle, it is coupled on an extruder, which provides a continuous band of rubber, and this material is placed over the roller surface. Instrumentation for designating a PLC and two inverters that control movements mentioned above, also an HMI screen wherein the operator enters data for coating as diameter, length of roll and the material delivery rate is used. Three sensors, strategically placed which provide data such as the presence of the polymer, ensuring that the process develops normally, material thickness which help synchronize spindle speeds and saddle, the last sensor measures the longitudinal displacement are also placed saddle in order to cover only the distance that the operator enters via the HMI.